2017
DOI: 10.1111/jan.13354
|View full text |Cite
|
Sign up to set email alerts
|

Comparing anger, anger expression, life stress and social support between Korean female nursing and general university students

Abstract: Becoming proficient in beneficial anger expression techniques and reducing stress from same-sex peer relationships will reduce anger among female nursing students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
0
11
0
2
Order By: Relevance
“…Previous studies reported that anger was one of the negative emotions displayed by nursing students in response to stress [3]. According to a study involving female college students in Korea, levels of anger in nursing students were significantly higher relative to those observed in other college students [8]. Moreover, nursing students' anger requires effective management as it could exert a negative impact on the quality of nursing, which could affect patients, the students, and future healthcare providers [4,6,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that anger was one of the negative emotions displayed by nursing students in response to stress [3]. According to a study involving female college students in Korea, levels of anger in nursing students were significantly higher relative to those observed in other college students [8]. Moreover, nursing students' anger requires effective management as it could exert a negative impact on the quality of nursing, which could affect patients, the students, and future healthcare providers [4,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Anger is an emotional response to stress, and numerous previous studies have shown that social stress increased levels of anger [3,8]. Therefore, stress could be regarded as an important factor that requires consideration in efforts to understand individuals' anger.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also indicates that the mediating effect of social support identified that life stress exerted a significant effect on social support. 11 Consequently, social support mediates the link between life stress and psychological outcome, such as stress and anger. For example, individuals are forced to gain support from their group members who are known to their problematic circumstances, they may show unfaithfulness and resentment and available support may be compromised.…”
Section: Introductionmentioning
confidence: 99%
“…Within nursing degrees, students have presented difficulties in reconciling personal, emotional and social demands with theoretical and practical academic activities, culminating in high levels of stress and, consequently, placing students at greater risk to health problems. [6][7] As a result, different responses can be triggered to handle difficult situations, for example, starting and/or maintaining abusive habits of legal and illegal drug use. On the other hand, future nurses are expected to work towards improving the health of the population, including care related to alcohol and drug abuse.…”
Section: Introductionmentioning
confidence: 99%